Non-uniform heating compensation for sequences of thermal images using median filtering (2013)
Herein, we introduce a new thermal contrast enhancement procedure for infrared images, acquired from a non-destructive evaluation of composite slabs through active infrared thermography experiments. This technique can compensate for the vignetting effect, as well as the non-uniform heating produced by the thermal excitation scheme. The proposed technique does not depend on any heat propagation model but almost exclusively on experimental data, because it is based on an unsharp mask operation using a median filter. The preliminary results show that real and apparent non-uniform heating is effectively compensated with this method, resulting in better images of possible internal defects than other classic methods like Differential Absolute Contrast (DAC), and therefore increasing the probability of more efficient detection and characterization procedures; specifically, the non-uniformity effect on the original sequence could be reduced by about 74%, according to a non-uniformity parameter defined in this work, as well.